Growth and Osteogenic Differentiation of Discarded Gingiva-Derived Mesenchymal Stem Cells on a Commercial Scaffold - Cristaldi, Marta; Mauceri, Rodolfo; Campisi, Giuseppina; Pizzo, Giuseppe; Alessandro, Riccardo; Tomasello, Laura; Pitrone, Maria; Pizzolanti, Giuseppe; Giordano, Carla (Frontiers in Cell and Developmental Biology, 2020)
Background In periodontal patients with jawbone resorption, the autologous bone graft is considered a “gold standard” procedure for the placing of dental prosthesis; however, this procedure is a costly intervention and poses the risk of clinical complications. Thanks to the use of adult mesenchymal stem cells, smart biomaterials, and active biomolecules, regenerative medicine and bone tissue engineering represent a valid alternative to the traditional procedures. Aims: In the past, mesenchymal stem cells isolated from periodontally compromised gingiva were considered a biological waste and discarded during surgical procedures. This study aims to test the osteoconductive activity of FISIOGRAFT Bone Granular® and Matriderm® collagen scaffolds on mesenchymal stem cells isolated from periodontally compromised gingiva as a low-cost and painless strategy of autologous bone tissue regeneration. Materials and Methods: We isolated human mesenchymal stem cells from 22 healthy and 26 periodontally compromised gingival biopsy tissues and confirmed the stem cell phenotype by doubling time assay, colony-forming unit assay, and expression of surface and nuclear mesenchymal stem cell markers, respectively by cytofluorimetry and real-time quantitative PCR. Healthy and periodontally compromised gingival mesenchymal stem cells were seeded on FISIOGRAFT Bone Granular® and Matriderm® scaffolds, and in vitro cell viability and bone differentiation were then evaluated. Results Even though preliminary, the results demonstrate that FISIOGRAFT Bone Granular® is not suitable for in vitro growth and osteogenic differentiation of healthy and periodontally compromised mesenchymal stem cells, which, instead, are able to grow, homogeneously distribute, and bone differentiate in the Matriderm® collagen scaffold. Conclusion Matriderm® represents a biocompatible scaffold able to support the in vitro cell growth and osteodifferentiation ability of gingival mesenchymal stem cells isolated from waste gingiva, and could be employed to develop low-cost and painless strategy of autologous bone tissue regeneration.